Experimental Study the Effect of Tool Design on the Mechanical Properties of Bobbin Friction Stir Welded 6061-T6 Aluminum Alloy - Amin, Samir Ali; Hanna, Mohannad Yousif; Mohamed, Alhamza Farooq (Al-Khwarizmi Engineering Journal, 2018)
Bobbin friction stir welding (BFSW) is a variant of the conventional friction stir welding (CFSW); it can weld the upper and lower surface of the work-piece in the same pass. This technique involves the bonding of materials without melting. In this work, the influence of tool design on the mechanical properties of welding joints of 6061-T6 aluminum alloy with 6.25 mm thickness produced by FSW bobbin tools was investigated and the best bobbin tool design was determined. Five different probe shapes (threaded straight cylindrical, straight cylindrical with 3 flat surfaces, straight cylindrical with 4 flat surfaces, threaded straight cylindrical with 3 flat surface and threaded straight cylindrical with 4 flat surfaces) with various dimensions of the tool (shoulders and pin) were used to create the welding joints. The direction of the welding process was perpendicular to the rolling direction for aluminum plates. Tensile and bending tests were performed to select the right design of the bobbin tools, which gave superior mechanical properties of the welded zone.  The tool of straight cylindrical with four flats, 8 mm probe and 24 mm shoulders diameter gave better tensile strength (193 MPa), elongation (6.1%), bending force (5.7 KN), and welding efficiency (65.4%) according to tensile strength.